Analisis Sebaran Fasilitas Pendidikan Sekolah Menengah Atas Negeri Di Kabupaten Boyolali - Noviana, Ina; , Drs. Priyono, M.Si; , Dra. Umrotun, M.Si (2016)
The distribution of senior high school(SMA) educational facilities has not been the same in each sub-district. Based on data from the Central Beaurau of statistics there are four sub districts that don,t haven senior high school education facilities, namely Selo, Mojosongo, Palm, and Juwangi. This difference may caused the difference of human resources quality in those sub district. The purpose of this research are (1) examine the pattern of the educational facilities of state senior high school in Boyolali Regency, (2) analyze every factor that influence the distribution of senior high school educational facilities, and (3) identify where are the students of senior high school came from. The methods used in this research is a survey backed by a secondary data analysis. Data analysis using the technique of classification and skoring. Assisted data processing using geographic information systems (GIS). The results obtained from this research are (1) High school education facilities spread Over the country in the area of research has spread patterns (dispersed); (2) factors that influence on the spread of education facilities is accessibility, availability of on-site educational services, the population trend in utilizing educational facilities, and quality schools (klas average national exam in Boyolali Regency low); and (3) the origin of the pupils in the study area is of 72.5% came from within the district, 27.5% coming from outside the districts, and 0.1% coming from outside the district. The average student of origin in the research area in relatively large because the school relatively close distance, good quality, as well as adequate infrastructure and facilities.